2006
DOI: 10.1590/s1413-86702006000100006
|View full text |Cite
|
Sign up to set email alerts
|

Profile of antimicrobial resistance of bacteria isolated from cockroaches (Periplaneta americana) in a Brazilian health care institution

Abstract: Cockroaches carry microorganisms to sterilized materials, equipment and non-contaminated food in hospitals and in homes. Hence, they are regarded as major microbial vectors. We isolated and identified microorganisms from living cockroaches captured from a Brazilian health care institution and we determined the antimicrobial susceptibility profile of the isolates. Following collection, cockroaches were immobilized at 4 degrees C for 10 to 20 minutes, immersed in 0.8% saline solution and then homogenized. Next, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
23
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 8 publications
4
23
0
1
Order By: Relevance
“…Insecta. Public Health.Some non-biting flying insects, particularly the common housefly (Musca domestica), have sporadically been described as possible mechanical vectors of agents of nosocomial infections because they may carry human pathogens and also due to their ubiquity including in the hospital environments 1-4 .In Brazil, there are some reports showing that ants and cockroaches harbor pathogens in hospitals 5,6 , but there is no report on non-biting flying insects. Therefore, our aim was to investigate the presence of potentially pathogenic bacteria on the external surface of flying insects collected inside a Brazilian health care institution.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Insecta. Public Health.Some non-biting flying insects, particularly the common housefly (Musca domestica), have sporadically been described as possible mechanical vectors of agents of nosocomial infections because they may carry human pathogens and also due to their ubiquity including in the hospital environments 1-4 .In Brazil, there are some reports showing that ants and cockroaches harbor pathogens in hospitals 5,6 , but there is no report on non-biting flying insects. Therefore, our aim was to investigate the presence of potentially pathogenic bacteria on the external surface of flying insects collected inside a Brazilian health care institution.…”
mentioning
confidence: 99%
“…In Brazil, there are some reports showing that ants and cockroaches harbor pathogens in hospitals 5,6 , but there is no report on non-biting flying insects. Therefore, our aim was to investigate the presence of potentially pathogenic bacteria on the external surface of flying insects collected inside a Brazilian health care institution.…”
mentioning
confidence: 99%
“…As cockroaches are the exclusive hosts of A. compressa larvae, representing both their food source and microenvironment, the wasp larvae need effective defense mechanisms against competitive, putrefactive, and pathogenic microbes (8)(9)(10)(11)(12)(13). In this study, we found clear evidence that A. compressa larvae are capable of coping with antagonistic microbes inside their P. americana hosts by using a mixture of antimicrobials present in their oral secretion.…”
Section: Discussionmentioning
confidence: 99%
“…S. marcescens (Enterobacteriaceae) is a ubiquitous, Gram-negative bacterium and a common colonizer of cockroaches (10)(11)(12)(13). It is responsible for food contamination (26) and causes disease in plants (27), invertebrates (4,26,28), and vertebrates, including humans (29).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation